Children's Critical Thinking Development Through Educational Toys with the Theme of Eruption Mountains in Children Aged 4-5 Years - Hidayah, Fifi Rofina Al; Naily Inayatul Maghfirah (JOYCED: Journal of Early Childhood Education, 2025)
The development of critical thinking skills in early childhood is a crucial aspect that must be stimulated and nurtured through appropriate approaches. This study aims to enhance children's critical thinking abilities through the use of an educational play tool themed volcanic eruption at RA Bustanul Ulum Badean Bangsalsari Jember. A descriptive qualitative method was employed, utilizing observation, interviews, and documentation to obtain an in-depth picture of the learning process in the field. The findings indicate that the volcanic eruption educational play tool serves as an effective learning strategy for fostering children's critical thinking skills. This is evident in the active involvement of children during exploratory activities, from constructing to practicing with the tool, which encourages them to observe, ask questions, and draw conclusions independently. Through this process, children develop reasoning abilities that form the fundamental basis of critical thinking.